"At Least Somebody Sees You as a Hero": Fatherhood Stress and Well-Being in Ghana. Issue 6 (November 2022) - Bowen, Anna; Chen, Y. Michael; Kodam, Ruth Sally; Odoi, Julius Amesimeku; Anto-Ocrah, Martina
Fathers' mental health and behaviors influence child development and partner well-being, yet paternal stress and well-being are frequently overlooked; especially in non-Western settings. The aim of this mixed-methods study was to quantitatively assess the impact of parenting stress on fathers' overall well-being in Ghana, West Africa; while qualitatively delving into their lived experiences as fathers. We used a qual/quant mixed-methods approach in this study. The study was conducted in three distinct locations in Ghana (a) Ada, a rural community on the Southeastern coast; (b) Kumasi, an urban setting in upper Southern Ghana; and (c) Sunyani, a peri-urban setting in West-central Ghana. Paternal stress was measured with the Aggravation in Parenting Scale (APS) and well-being was assessed using the Secure Flourishing Index (SFI). Textual data from focus group interviews were sorted using inductive coding and aggregated into overarching themes. Thirty-eight Ghanaian fathers ages 21 to 74 years participated in the study, average age 43 (±12.12 SD ), median 39.5. Correlation analyses showed a strong, negative association between paternal stress and well-being ( R = −0.63; p < .0001), which was supported in linear regression models (β = −1.04; 95% CI: −1.62, −0.45; p <.0001). Emergent themes of fatherhood stress included financial (employment, food, education, and health care), social (norms and expectations), and psychological (mental work, discipline, relationships, and coping strategies) stressors. A fourth overarching theme of pride and joy in parenting permeated the interviews. Ghanaian fathers with higher parenting stress experience lower overall well-being. Identified stressors could guide interventions that bolster the well-being of fathers and their families.